Optimal Monetary and Macroprudential Policy in a Currency Union - Benjamin Schwanebeck; Jakob Palek (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The financial crisis proved strikingly that stabilizing the price level is a necessary but not a sufficient condition to ensure macroeconomic stability. The obvious candidate for addressing systemic risk is macroprudential policy. In this paper we study the optimal (Ramsey) monetary and macroprudential policy mix in a currency union in the case of different kinds of aggregate and idiosyncratic shocks. The monetary and macroprudential instruments are modelled as independent tools. With a union-wide macroprudential tool, full absorption on the aggregate level is possible, but welfare losses due to fluctuations in relative variables prevail. With country-specific macroprudential tools, full absorption of shocks is always possible. But it is only optimal as long as there is no difference in the financing of production factors. Evaluating the performance of different policy regimes shows that the additional welfare gain from having country-specific macroprudential tools vanishes as the ability of the central bank to commit decreases.
Keywords: E58; E32; E44; 330